Parasite diversity of disease-bearing rodents of Southeast Asia: habitat determinants and effects on sexual size dimorphism and life-traits - Morand, Serge; Bordes, Frédéric (Frontiers in Ecology and Evolution, 2015)
We investigated a causal chain of relationships between habitat specialization and parasite species richness in rodent communities in Southeast Asia, and the consequences for variation in immune investment (using spleen size), the degree of sexual competition (using testes) and sexual size dimorphism (SSD). We used data gathered on rodents, their habitat specialization and their parasites (macro- and micro-parasites) in Southeast Asian landscapes. The results supported the hypotheses that parasite diversity drives the evolution of host life-traits and sexual selection. Firstly host habitat specialization explained the variation in parasite species richness. Secondly high parasite species richness was linked to host immune investment, using the relative spleen size of rodents. Thirdly according to the potential costs associated with immune investment, the relative spleen size was found to be negatively correlated with the relative size of testes among rodents. Fourthly, a positive relationship between male-biased SSD and parasite species richness was observed supporting the role of parasitism in sexual selection. Finally, the variation in SSD was positively associated with the degree of habitat specialization. Highest values of female-biased SSD were associated with habitat specialization, whereas highest values of male-biased SSD concerned synanthropic or generalist rodent species. These results, also correlative, will help to facilitate selection of the species that should be thoroughly investigated at the population level to better understand the selective effects of parasites on rodent life-history and behavior.